Transition from one- to two-mode generation regime in spin-torque nano-oscillator mediated by thermal noise - Slobodianiuk, D.V. (Condensed Matter Physics, 2014)
Two-mode model of spin-torque nano-oscillator (STNO) under the action of thermal noise is considered. Langevin equations for mode amplitudes were derived starting from general nonlinear oscillator model. Stationary probability distribution function describing mean mode generation powers was obtained using Fokker-Planck equation. It was shown that thermal noise can lead to two-mode generation in STNO. An increase of thermal noise power leads to excitation of the second mode in a system and to a two-mode generation regime through intermediate state when two modes coexist only in some range of the applied currents. Розглянуто модель магнiтного наноконтакту пiд дiєю теплового шуму. Виходячи з рiвнянь узагальненого нелiнiйного осцилятора, одержано рiвняння Ланжевена для амплiтуд мод. Використовуючи рiвняння
Фокера-Планка, було одержано вираз для стацiонарної функцiї розподiлу, що описує середнi значення
потужностей мод системи. Було показано, що тепловий шум в системi може призводити до двомодової
генерцiї. Збiльшення потужностi теплового шуму призводить до збудження другої моди в системi i встановлення двомодового режиму генерацiї через промiжний стан, коли в системi iснує двомодовий режим
генерацiї в обмеженiй областi величин зовнiшнiх струмiв.